Familial Chylomicronemia Syndrome Presenting With Acute Necrotizing Pancreatitis in a Five Month Infant - Borghei, Amirmasoud; Azizi, Mahba (Journal of Nepal Paediatric Society, 2010)
Familial chylomicronemia syndrome (FCS) is a rare disease characterized by severe fasting hypertriglyceridemia and chylomicronemia, which is inherited in an autosomal recessive manner. It is arisen from apolipoprotein C-ll deficiency or Lipoprotein Lipase(LPL) Deficiency.We report a 5-month-old male infant FCS presenting with acute abdominal pain and post surgical diagnosis of acute necrotizing pancreatitis. Key words: Pancreatitis; chylomicronemia; hyperlipidemia; lipoprotein lipase. DOI: 10.3126/jnps.v30i2.2431 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 110-112